2013
DOI: 10.12968/bjon.2013.22.14.813
|View full text |Cite
|
Sign up to set email alerts
|

Nurse management of cardiovascular risk factors in rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic, multi-system inflammatory disease. The incidence and prevalence of RA varies considerably between geographic areas and over time; the prevalence of RA in adults aged > 20 years in Spain is around 0.5% (Carmona et al, 2002). People with RA also have extra-articular manifestations, presenting an increased cardiovascular morbidity and mortality risk; therefore, cardiovascular risk screening and management strategies are necessary in individuals with RA. The importance of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
3
0
2
Order By: Relevance
“…Despite the fact that patients with RA have an similarly increased risk to that in diabetes van Halm et al, 2009), both our review, the country-specific descriptions and other studies indicate that the implementation of CVR assessment and management in patients with IA is still scarce, irrespective of whether this role is undertaken by rheumatologists, GPs or nurses (Garcia-Diaz and Corominas, 2013;Monk et al, 2013;Peters and Nurmohamed, 2013). Only two of the included studies described nurse-led CVR assessment and management in rheumatology (Dougados et al, 2015;Primdahl et al, 2013).…”
Section: Discussionmentioning
confidence: 85%
“…Despite the fact that patients with RA have an similarly increased risk to that in diabetes van Halm et al, 2009), both our review, the country-specific descriptions and other studies indicate that the implementation of CVR assessment and management in patients with IA is still scarce, irrespective of whether this role is undertaken by rheumatologists, GPs or nurses (Garcia-Diaz and Corominas, 2013;Monk et al, 2013;Peters and Nurmohamed, 2013). Only two of the included studies described nurse-led CVR assessment and management in rheumatology (Dougados et al, 2015;Primdahl et al, 2013).…”
Section: Discussionmentioning
confidence: 85%
“… Se reduciría el riesgo cardiovascular de los pacientes con AR establecida, gracias a la educación sobre hábitos saludables, dieta y ejercicio [122] .…”
Section: Alternativa Propuestaunclassified
“… Se mantendría un IMC adecuado en los pacientes con AR establecida como consecuencia de acudir a sesiones de dietética y nutrición [122] .…”
Section: Alternativa Propuestaunclassified
“…A study by Garcia-Diaz and Corominas, in Spain, entitled "nursing management for risk factors for cardiovascular disease in rheumatoid arthritis" showed that rheumatologist nurses are in a position well suited to include a routine risk assessment for cardiovascular disease for RA affected people. They are in a position to do well with the usual risk assessment of cardiovascular disease for those with RA referred to the clinic and provide educational interventions to reduce the risk of cardiovascular disease, such as smoking cessation, weight loss, bal-anced eating, low-fat diet, and regular exercise (19). In fact, although traditional cardiovascular (CV) risk factors are more prevalent in RA than in the general population, they do not adequately account for the increase in CV morbidity and mortality observed in these patients.…”
Section: Introductionmentioning
confidence: 99%